The Mother's Day Geomagnetic Storm on 10 May 2024: Aurora Observations and Low Latitude Space Weather Effects in Mexico - J. A. Gonzalez‐Esparza; E. Sanchez‐Garcia; M. Sergeeva; P. Corona‐Romero; L. X. Gonzalez‐Mendez; J. F. Valdes‐Galicia; E. Aguilar‐Rodriguez; M. Rodriguez‐Martinez; C. Ramirez‐Pacheco; C. I. Castellanos; M. Pazos; B. Mendoza; et al. (Space Weather)
Abstract On 10 May 2024, a severe geomagnetic storm coinciding with Mother's Day in Mexico lasted over 40 hr and produced polar auroras observable at low latitudes. This storm, the most intense since 2003, resulted from a series of solar flares and coronal mass ejections from active region 3664. The event was significant for space weather studies in Mexico, marking a milestone by enabling comprehensive measurements of its effects. The Mexico Space Weather Service (SCIESMEX) and the National Space Weather Laboratory (LANCE) had prepared for such an event since their inception. LANCE's instrument networks recorded solar chromospheric images, solar radio bursts, geomagnetic variations, Schumann resonances, ionospheric disturbances, and energetic particle flows. They also monitored Geomagnetically Induced Currents (GICs) in three strategic substations of the national electrical system. This provided unprecedented insights into the dynamics of severe space weather events at the North‐American low‐latitude environment. Citizen science efforts documented auroras and regional responses, capturing variations in geomagnetic indices, ionospheric disturbances, cosmic ray fluxes, GICs, and technological impacts. SCIESMEX worked with the National Civil Protection System (SINAPROC) to issue warnings, ensuring public awareness and preparedness. This coordination underscores the importance of effective communication and collaboration in mitigating impacts. The May 2024 geomagnetic storm demonstrated the critical role of preparedness, research, and public education in reducing the effects of future space weather events in Mexico.